The willingness to pay for mortality risk reductions: A comparison of the United States and Canada - Anna Alberini; Alan Krupnick; Maureen Cropper; Nathalie Simon; Joseph Cook (Fondazione Eni Enrico Mattei (FEEM), 2001)
We present the results of two contingent valuation surveys conducted in Hamilton, Canada and nation-wide in the US to elicit WTP for reductions in one's risk of death. We find that the Values of a Statistical Life implied by WTP are very similar across the two studies, and range from 930,000 to 4.8 million (2000 US dollars). WTP increases with the size of the risk reduction, but varies little with the age of the respondents: people older than 70 years of age hold WTP values that are about one-third lower than those of other respondents. This effect is significant in Canada but not in the US. Health status of the respondent has limited effect on WTP. In general, these results provide only little or no evidence that VSL used in environmental policy analyses should be adjusted for the age or health status of people whose lives are saved by environmental policies.
Keywords: I18; Q28; 330; Value of a Statistical Life; mortality risks; benefit-cost analysis; Gesundheit; Willingness to pay; Sterblichkeit; Vergleich; USA; Kanada